Diagnosis of post-attenuation neurological signs syndrome in a cat with refractory status epilepticus and clinical response to therapeutic plasma exchange. Issue 2 (September 2022) - Niemann, Lisa; Beckmann, Katrin; Iannucci, Claudia; Wang Leandro, Adriano; Vigani, Alessio
Case summary: An 8-year-old female spayed British Shorthair cat that underwent surgical portosystemic shunt (PSS) attenuation developed progressive neurological signs 7 days postoperatively. Neurological signs progressed, despite medical management, and seizure activity became rapidly refractory to anticonvulsants. The diagnosis of post-attenuation neurological signs (PANS) was made based on the timing of the occurrence of clinical signs following surgery, absence of hyperammonaemia and suggestive MRI findings of the brain. The cat developed status epilepticus that required treatment with general anaesthesia and mechanical ventilation, from which the cat could not be effectively weaned without the recurrence of seizures. Therapeutic plasma exchange (TPE) was performed as a rescue therapy for PANS and associated refractory status epilepticus. A total of two plasma volumes were processed during one single TPE session. The seizure activity resolved immediately after the TPE session, the cat showed progressive improvement of neurological signs and remained stable thereafter. No significant complications associated with the TPE were observed. The cat was discharged 11 days after admission and was fully recovered. Relevance and novel information: This is an unusual report of PANS diagnosed in a cat based on clinical and MRI findings. The cat developed refractory status epilepticus and had a positive outcome following TPE as rescue therapy. The MRI findings in this report could be useful for the diagnosis of PANS in cats. We speculate that TPE could be taken into consideration as a possible therapeutic intervention in PANS syndrome.